Job skill assessment of pharmacy students in South Karnataka: A cross-sectional study - Shanthi Lysetty, Anup Naha, Usha Yogendra Nayak, Virendra S. Ligade, Bhavana B. Bhat, Usha Rani (Journal of Applied Pharmaceutical Science, 2023)
This study aims to assess the knowledge of pharmacy students about the job skills required by the pharmaceutical industry in Karnataka, India. A cross-sectional study was conducted in pharmacy colleges using a cluster random sampling technique. The validated questionnaire was given to pharmacy students, and the response was collected and analyzed. The questionnaire response rate was 65%. The mean age of the respondents was 21, with a standard deviation of 0.77. The study findings indicate that 94% of students have poor skills. Only 10% of students responded to communication skill-based questions. The questions based on critical thinking and analytical skills were answered by 24% and 14% of students, respectively. In comparison, the questions on problem-solving skills were responded to by 5% of students. One proportion test was done for all the questions, and students’ knowledge was less than 50%. Thus it is essential to improve the professional skills among the students so they will get jobs in this fast-changing and competitive world. The study also suggests a need to upgrade the pharmacy curriculum as per industry needs. Further, there is a need to incorporate training modules as part of the syllabus and bridge the gap between academia and industry.